Eco-literasi PENINGKATAN ECOLITERACY SISWA SEKOLAH DASAR MELALUI PROGRAM PENGABDIAN MASYARAKAT : - - I Made, Putrawan (Farabi, 2025)
The development process around the world is faced with a dilemma, namely whether development keep going continued, consider the impact it causes, namely damaging environment. One proof is and more it's hot earth's temperature as a result of clearing forests for the sake of generating development various crisis environments is one of them is global warming. This is thought to be caused by the "ignorance" factor of world leaders about concepts-based ecology. Therefore, giving knowledge and understanding since early to generation young people, especially students, about concepts based on “eco-literacy,” is urgent to do. Based on this thought, it is necessary to implement the activity in the form of devotion in society (P2M), especially for students in Elementary School, to improve eco-literacy through delivery in the form instructional pack. One of the methods to evaluate the success of a service program public is based on the evaluation initial (before the program is implemented) compared to the results end (after the program is done), so it looks at whether there is improvement in a way significant or not. If there is, then can it be said that the P2M program was successful? The methods applied are, at the beginning of activities, visiting the school, then the team giving an explanation and then giving test pre-test to the students, and then sharing a small book called learning package about eco-literacy. After around one-half month, with the students' estimates already reading the learning package contents, the team came back to class and provided a post-test. The difference between the two tests found there was an improvement in students' eco-literacy significantly, so it can be concluded that the P2M program implemented was successful. Based on this activity, recommendations could be delivered that in every learning, teachers are asked to always tuck in basic concepts, for early use to improve students’ eco-literacy, therefore, in the future, they are the ones who will become national leaders.